“Mendidik dengan Hati dan Keteladanan”: Branding untuk Menumbuhkan Karakter Pendidik Anak Usia Dini - Sri Wahyuni; Ellyn Sugeng Desyanty; Rezka Arina Rahma (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2020)
This study aims to explain the form of character building for early childhood educators through brand "educating with heart and exemplary" and how the role of the principal in translating the branding to all school members. This research was conducted with a case study research design at the As Salam PAUD institute in Malang. Data collection is done by observation, interview and document study techniques. Data analysis was performed using an interactive analysis technique of the Miles and Huberman model which included stages of data reduction, data display, and verification, all of which were carried out interactively. While the validity test of the findings is carried out using the source tringulation technique, method, time, and by extending the observation. The results of this study indicate that the activities of educating the character of educators are carried out through brand to “educating with heart and exemplary” which are manifested in three forms of activities, namely the application of a typical learning curriculum, which requires the exemplary of an educator; the application of variations of morning activities for children to transmit the positive character of educators to children; and organizing "halaqoh" activities to build the character of all educators. The role of the principal in this effort is as a role model and motivator for educators, employees and children, as well as supervisors for character development.